Glycan degradation in Polygonati Rhizoma: Effects of traditional ‘nine steaming and nine basking’ on low molecular weight Fructans and polysaccharides - Xingyu Mei; Jiabei Xia; Wenqing Li; Yufen Wu; Huan Cheng; Shiguo Chen; Xingqian Ye; Jianle Chen (Food Chemistry: X)
The traditional “nine steaming and nine basking” method for processing Polygonati Rhizoma has been practiced in China for over two millennia. However, research on its impact on glycans, particularly low molecular weight fructans, is limited. Therefore, dynamic changes in glycans were analyzed based on the two common species, Polygonatum filipes and Polygonatum cyrtonema. Results revealed the significant degradation of low molecular weight fructans within the first three processing cycles, with complete degradation by the seventh cycle, suggesting that the traditional technique may be excessive. Molecular weight analysis indicated the aggregation, degradation, and reaggregation of polysaccharides, with a notable decrease in fructose and an increase in galactose. This suggested that fructans were the primary constituents before processing, while galactans prevailed afterward. No significant differences in carbohydrate changes were found between the two species. This study enhances our understanding of the traditional processing mechanisms and promotes the efficient utilization of Polygonati Rhizoma.